Biomass burning organic aerosol from prescribed burning and other activities in the United States. (15th November 2020) - Theodoritsi, Georgia N.; Posner, Laura N.; Robinson, Allen L.; Yarwood, Greg; Koo, Bonyoung; Morris, Ralph; Mavko, Matthew; Moore, Tom; Pandis, Spyros N.
Abstract: A three-dimensional chemical transport model, PMCAMx-SR, was applied in the continental U.S. to investigate the contribution of prescribed burning and other biomass burning sources to the total organic aerosol (OA) concentrations. Simulations were performed during three seasonally-representative months (April, July and September 2008). Prescribed biomass burning organic aerosol (bbOA) emission rates were estimated to be approximately 300, 80 and 250 tn d −1 during April, July and September respectively. Prescribed burning was limited during July due to the prevailing weather conditions. Prescribed burning is responsible for 45% of the total bbOA emissions during the simulated spring period, 20% during the fall, and just 3% during the summer. The predicted maximum hourly prescribed bbOA concentration reached approximately 100 μg m −3 during April in South Carolina and during September in New Mexico, whereas it was less than 15 μg m −3 during July in Arkansas. The average contribution of prescribed burning to OA in the continental U.S. is quite low (less than 5%) and 60–70% is predicted to be secondary OA. Biomass burning secondary organic aerosol (bbSOA) levels far away from the prescribed fires are predicted to exceed 2 μg m −3 . In states with intensive prescribed burning activities this source is predicted to contribute 20–40% of the OA on a monthly average basis. In these states (for example South Carolina during April), the predictions reveal that people can be exposed for 20 h per month on average to bbOA levels exceeding 5 μg m −3 and for 200 h to levels above 0.5 μg m −3 . This should be contrasted to 220 h of exposure to bbOA above 5 μg m −3 and 650 h to bbOA above 0.5 μg m −3 for states and periods with intense wild fires (for example California during July). Highlights: Prescribed burning contributes 20–40% of organic aerosol in some US states. The average contribution of prescribed burning to OA in the US is less than 5%. On average 60–70% is predicted to be secondary OA. Exposures to OA from prescribed burning are significant but lower than wildfires.